Beyond science literacy (re) reading science communication from a development communication perspective - Montemayor, Garry Jay S. (The Philippine Journal of Development Communication, 2013)
This essay explores the idea of discoursing science communication (scicom) Devcom style outside the arguments of science literacy. This was done by putting the different science communication models synthesized by Brossard and Lewenstein (2010) vis-a-vis Craig's (1999) traditions of communication, Roman's (2005) traditions in development communication, and Melkote and Steeves' (2001) development communication frameworks. The paper puts forward that scicom models and Devcom concepts have the same roots of epistemological assumptions, making them seemingly identical in goals and perspectives. Mapping the scicom models with Devcom tradition and frameworks not only explains to us their connection, but also paves the way to rethink how we can diversify our scicom instruction, research, and practice were discussed.